2018
DOI: 10.1080/14330237.2018.1438832
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leadership, followership, and psychological capital as antecedents of work engagement

Abstract: The present study investigated authentic leadership, psychological capital, and followership behaviour influences on work engagement of employees . Respondents were 901 South African employees within the healthcare industry organisation (n = 647) and mining industry (n = 254) . The employees completed questionnaires on authentic leadership, psychological capital, and followership behaviour, and work engagement . Results following structural equation modelling and mediation analysis suggest work engagement to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…When employees encounter setbacks, authentic leadership helps them cope positively, thus increasing their resilience (Ilies et al, 2005). Research suggests that authentic leadership positively predicts psychological capital (Hu et al, 2018; Hu et al, 2018; Plessis & Boshoff, 2018).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…When employees encounter setbacks, authentic leadership helps them cope positively, thus increasing their resilience (Ilies et al, 2005). Research suggests that authentic leadership positively predicts psychological capital (Hu et al, 2018; Hu et al, 2018; Plessis & Boshoff, 2018).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…It is important to note that findings from international studies cannot simply be extrapolated for use within the South African context, as authors argue that leadership is contextually based ( Scheepers and Elstob, 2016 ; Lemoine et al, 2019 ). Second, AL remains somewhat unexplored in the mining sector as the majority of research is focused on the healthcare sector ( Boamah et al, 2016 ; Coxen et al, 2016 ; Du Plessis and Boshoff, 2018b ) or a combination of healthcare and mining ( Du Plessis and Boshoff, 2018a ). The challenges faced by leaders (and their subordinates) in the mining industry (i.e., more physical) is vastly different from those experienced in the healthcare industry (i.e., more emotional).…”
Section: Introductionmentioning
confidence: 99%
“…The topic of authentic leadership has become more prominent in recent years in both practical and academic fields (Agote, Aramburu, & Lines, 2015;Coxen et al, 2016;Du Plessis & Boshoff, 2018;Shamir & Eilam-Shamir, 2018;etc.). Previous studies have indicated that authentic leadership may have a positive effect on psychological safety (Eggers, 2011), trust in supervisors (Caldwell & Dixon, 2010;Coxen et al, 2016) and work engagement (Walumbwa, Avolio, Gardner, Wernsing, & Peterson, 2008;Walumbwa, Wang, Wang, Schaubroeck, & Avolio, 2010).…”
Section: Introductionmentioning
confidence: 99%